Implementasi Pendekatan Konstruktivisme dalam Menanamkan Nilai Religius Hadis Kebersihan pada Siswa Sekolah Dasar - Salsabila Nurul Fidia; Aninditya Sri Nugraheni; Risky Pratama; Yulia Angga Anggraini; Zulfadhli Zulfadhli (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to describe the implementation of a constructivist approach in instilling religious values through the Hadith on cleanliness among elementary school students. Constructivism emphasizes the active role of students in constructing knowledge through direct experience and personal reflection. The research method used is a literature review, analyzing various sources related to constructivist education and the teaching of Islamic values in elementary education. The findings indicate that the constructivist approach can be effectively applied through contextual learning strategies, group discussions, and hygiene-related practices linked to the values of Hadith. This implementation not only improves students’ understanding of the importance of cleanliness in Islam but also fosters consistent religious attitudes in their daily lives. Thus, integrating Islamic values into constructivist-based learning contributes positively to students’ character development.